Optimizing Bandwidth Priority Distribution using Mikrotik with Quality of Service (QOS) techniques - Taufiq Ramadhan; Muhammad Zen; Hafni (Cattleya Darmaya Fortuna, 2026)
phones consume up to 15 Mbps of bandwidth allocation, laptops 18 Mbps, and computers 59 Mbps without any priority for CCTV. After implementing QoS through Simple Queue, mobile phone consumption was successfully limited to 4.7 Mbps, laptops to 7.6 Mbps, and computers to 28 Mbps, while CCTV was set as the main priority with a bandwidth distribution allocation of 60 Mbps. The results of this study prove that implementing bandwidth management with the QoS method is able to create a more stable connection, even distribution of internet, and according to the needs of each device